Robotically performed excimer laser coronary atherectomy: Proof of feasibility. Issue 4 (9th March 2018) - Almasoud, Abdullah; Walters, Daniel; Mahmud, Ehtisham
Abstract: The feasibility, safety, and high technical success of robotically assisted percutaneous coronary intervention (PCI) for the treatment of both simple and complex coronary disease has been demonstrated. As the current generation robotic platform is limited to a rapid exchange system, orbital or rotational atherectomy cannot be performed robotically. However, excimer laser coronary atherectomy is performed with a rapid exchange catheter but its feasibility during robotically assisted PCI is unknown. We report the successful use of laser atherectomy during two complex robotically assisted PCI procedures using the CorPath GRX robotic system.